2017
DOI: 10.1093/ndt/gfx005
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced renal inflammation is ameliorated by cilastatin nephroprotection

Abstract: Cilastatin reduces cisplatin-induced nephrotoxicity, which is associated with decreased inflammation in vivo. Although the exact role of decreased inflammation in nephroprotection has not been fully elucidated, treatment with cilastatin could be a novel strategy for the prevention of cisplatin-induced acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 60 publications
6
62
0
Order By: Relevance
“…Therefore, cilastatin, which fully restores both PI (38:4) and LPI(18:0) and tends to restore other PI species too, is able to block cisplatininduced apoptosis and its downstream effects. These results show, for the first time, the underlying process of our previous observations (10,12,15). Moreover, other phospholipids, such as PC, can also be a source of AA via PLA2.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, cilastatin, which fully restores both PI (38:4) and LPI(18:0) and tends to restore other PI species too, is able to block cisplatininduced apoptosis and its downstream effects. These results show, for the first time, the underlying process of our previous observations (10,12,15). Moreover, other phospholipids, such as PC, can also be a source of AA via PLA2.…”
Section: Discussionsupporting
confidence: 75%
“…2 and 4). Cisplatin activates nuclear factor kappa  [thus triggering an increase in proinflammatory molecules and interleukins (15)], which can induce PLA2 (59). In addition, cisplatin is able to increase production of inflammatory species (15) during renal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrated that cilastatin also protected against the nephrotoxicity of diclofenac. In a previous study, cisplatin induced oxidative stress, inflammation and apoptosis, which could be inhibited by the co‐administration of cilastatin (Humanes et al, ; Humanes et al, ). In the present study, diclofenac also induced elevated levels of oxidation products, cytokine production and apoptosis in the kidney (Figures b and a), which was consistent with the results of a previous study (Fattori et al, ) and could be prevented by cilastatin treatment.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism of anticancer impact of cisplatin is an interaction with purine base DNA function, which leads to stopping the proliferation of tumor cells and inducing apoptosis (8). Free oxidant radicals reduce glomerular filtration and cause acute nephrotoxicity in the tubules, particularly S3 segment of proximal tubules (9) The complications of cisplatin Cisplatin has numerous side effects, one of them is nephrotoxicity by inflammation in the interstitial tissue (10). Hypomagnesemia is another complication which is due to loss of magnesium through the urine because of damage to the thick, ascending part of Henle loop and distal tubules.…”
Section: Mechanisms Of Cisplatin Actionmentioning
confidence: 99%